A novel optimization method for wind power investment considering economic and security concerns - Ayvaz, Alisan; Genc, Istemihan (AIP Publishing, 2022)
This paper proposes a novel optimization method for wind power investment to find the optimal location and sizing of multiple wind farms considering both the economic and security aspects of power system operation and planning. The proposed approach maintains the system's security against transient instabilities while improving the voltage profile in the network and minimizing the cost resulting from the investment of wind farms and their operation with thermal units. The transient stability assessment is performed for the power system, considering the uncertainties due to its wind power generation. To model these uncertainties, Taguchi's orthogonal array testing method is utilized. Using Taguchi's method, all the uncertainties in an optimization problem are modeled with only a few representative testing scenarios, and thus, it provides computation efficacy. Moreover, an enhanced hybrid algorithm combining the particle swarm and gray-wolf optimization methods is developed to obtain efficient results in solving the problems formulated. The proposed wind power investment approach is implemented on the New England 39-bus test system, and the results show its effectiveness in providing a reliable and economic wind investment strategy for both investors and operators in the long-term operation and planning of the power system.